2012
DOI: 10.1016/j.juro.2012.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Lymph Node Dissection with Adjuvant Radiotherapy for Nodal Recurrence of Prostate Cancer

Abstract: Based on (11)C/(18)F-choline positron emission tomography-computerized tomography as a diagnostic tool, salvage lymph node dissection is feasible for the treatment of nodal recurrence of prostate cancer. Most patients experience biochemical recurrence after salvage lymph node dissection. However, a specific population has a lasting complete prostate specific antigen response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 29 publications
10
65
0
10
Order By: Relevance
“…There is also the option to perform salvage lymph node dissection of the pelvis with (25,26) or without (27,28) adjuvant radiotherapy, taking into account that adjuvant irradiation results in delayed relapse within the treated region, but has no effect on the relapse pattern outside the treated region. Therefore, the combination of two local treatment modalities within the same anatomic region does not offer any additional benefit for patients with prostate cancer (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also the option to perform salvage lymph node dissection of the pelvis with (25,26) or without (27,28) adjuvant radiotherapy, taking into account that adjuvant irradiation results in delayed relapse within the treated region, but has no effect on the relapse pattern outside the treated region. Therefore, the combination of two local treatment modalities within the same anatomic region does not offer any additional benefit for patients with prostate cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of two local treatment modalities within the same anatomic region does not offer any additional benefit for patients with prostate cancer (27). In addition, surgery has the risk of common perioperative complications (25)(26)(27)(28). To our knowledge, no prospective studies comparing salvage lymph node dissection with or without radiotherapy using PSMA-PET/CT for staging purposes have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Impressively, the 8-year cancer-specific mortality-free survival and biochemical recurrence-free rates were 81 and 23%, respectively. Similarly, a German group found that 46% experienced complete biochemical response after salvage pelvic lymph node dissection [26]. Just under half of this cohort received adjuvant radiotherapy following lymph node dissection but this subset of men did not exhibit an advantage in preventing clinical progression.…”
Section: Superior Detection Of Bone Metastasesmentioning
confidence: 95%
“…A. Jilg и соавт. оценили данные 52 пациентов, которым провели первичное лечение по поводу РПЖ [27]. У всех больных зарегистрирован биохимический рецидив и выявлены метастатические очаги в ЛУ по данным ПЭТ / КТ, а также подтверждено отсутствие отдаленных метастазов.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified